2000
DOI: 10.1002/ddr.1
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric modulation of the rat adenosine A1 receptor: Differential effects on agonist and antagonist binding

Abstract: The interaction of 2-amino-3-benzoyl-thiophene derivative, PD81,723, as well as other G protein-coupled receptor (GPCR)-modulating agents such as suramin (SUR), N-ethylmaleimide (NEM), GTP, and NaCl with the rat adenosine A 1 receptor was investigated using kinetic, saturation, as well as displacement experiments of various agonists, partial agonists or antagonists. PD81,723 enhanced agonist (CPA, R-PIA, NECA) binding ~2-fold, while its effect on CPA binding was increased (4-11-fold) with other modulators pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…However, several residues have been demonstrated to be critical to the modulation of either PD 81,723 or sodium ions. The mutation of Thr277 (7.42) to Ala not only decreased agonist affinity but also inhibited the effects of PD 81,723 [23]. Studies of the D55A 2.50 mutant A 1 AR revealed that Asp55 is responsible for allosteric regulation of binding by sodium because the affinity for [ 3 H]CCPA did not change over broad ranges of sodium concentrations [22].…”
Section: A 1 Arsmentioning
confidence: 99%
“…However, several residues have been demonstrated to be critical to the modulation of either PD 81,723 or sodium ions. The mutation of Thr277 (7.42) to Ala not only decreased agonist affinity but also inhibited the effects of PD 81,723 [23]. Studies of the D55A 2.50 mutant A 1 AR revealed that Asp55 is responsible for allosteric regulation of binding by sodium because the affinity for [ 3 H]CCPA did not change over broad ranges of sodium concentrations [22].…”
Section: A 1 Arsmentioning
confidence: 99%
“…Diabetes mellitus is a condition characterized by chronically elevated levels of blood glucose caused by incorrect function of the hormone responsible for the hGCRG activation. Because the structure-based drug design program through substituted 2aminothiophenes has been investigated broadly, up to this date there are many other research works dealing with the synthesis, pharmacology and application of thiophenebased structures in medicinal chemistry (KOUROUNAKIS et al, 2000). It is no doubt, that this area of Gewald-like thiophene derivatives exhibits the highest progress in a scope and utilization.…”
Section: Other Important Pharmaceuticals Developed From2-aminothiophenesmentioning
confidence: 99%
“…The synthesis of these latter two series of compounds is described in Scheme . The preparation of alkylated piperidones 12 − 18 was performed following the procedure of IJzerman,18a which consists of the reaction of the commercially available hydrochloric salt of 4-piperidone with the appropriate substituted benzyl chloride. For the synthesis of N -[(3-pyridyl)methyl]-4-piperidone 21 , acylation of 4-piperidone ethylene acetal with nicotinoyl chloride produced the amide 19 in good yield.…”
Section: Chemistrymentioning
confidence: 99%
“…To study the role of various substitutions on the phenyl ring and the importance of the 4,5-dimethyl group on the thienyl ring, Baraldi, IJzerman, and Tranberg 19 have described the synthesis and biological evaluation of mostly novel PD 81,723 analogues. It was evident from previous SAR studies that substitution with electron-withdrawing substituents, such as chlorine and trifluoromethyl, on the benzoyl moiety at the 3-position of the thiophene ring resulted in higher enhancement activity. …”
Section: Introductionmentioning
confidence: 99%